Segara Kerthi as The Foundation of Hospitality Education Strengthening Marine Environmental Awareness Among Students : Segara Kerthi Sebagai Fondasi Pendidikan Perhotelan Memperkuat Kesadaran Lingkungn Laut Di Kalangan Mahasiswa - I Wayan Agus Anggayana; Rosvita Flaviana Osin; Rizki Sumardani; Fenny Sengkey; I Gede Wiramatika; Retny Asriyani; Ni Putu Lindawati (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
This study aims to comprehensively explore the implementation of the Segara Kerthi concept as a foundational element within hospitality education, with a specific focus on enhancing marine environmental awareness among students in the University. The research was conducted in Bali, involving a sample of 20 students who participated as respondents. The research method employed a qualitative approach, utilizing various data collection techniques, including in-depth interviews, participant observations, and thorough document analysis, to obtain a comprehensive understanding of the subject matter. The results of this study reveal that the integration of the Segara Kerthi concept into the hospitality education curriculum has a profound impact on increasing students' awareness, knowledge, and appreciation of the importance of preserving marine environments. The students who participated in this study not only exhibited a deeper understanding of marine environmental issues but also demonstrated a heightened level of engagement and active participation in marine conservation activities. This indicates that the educational strategies employed were effective in fostering a strong environmental ethic among students, particularly concerning marine ecosystems. The conclusions drawn from this research suggest that the Segara Kerthi concept serves as a valuable and effective framework for embedding environmental consciousness within the hospitality education sector. Based on these findings, the study recommends that the Segara Kerthi concept be widely adopted and implemented across various hospitality education programs. Additionally, it suggests that collaborative efforts involving multiple stakeholders, including educators, industry professionals, and environmental organizations, be strengthened to enhance the effectiveness of marine environmental conservation initiatives. The scope of this study was limited to students from the Community Academy. Therefore, it is recommended that future research expand the sample size and include a more diverse population to validate and extend the findings of this study.